Examination of endoscopic intracanal observation with an ultrafine‐diameter scope - Takeshi Jinno; Kazuya Miyaguchi; Daiki Muraishi; Toshiyuki Narumi; Kanji Kabasawa; Hideki Ohgo; Yoshikazu Tsuzuki; Hiroyuki Imaeda (DEN Open)
Abstract Objectives The endoscopic channel can be damaged by instruments during use and cleaning, leading to contamination, infection, and increased repair costs. However, few devices are available to observe the inside of the endoscopic channel. This study employed an ultrafine‐diameter scope to examine damage in the endoscopic channel. Methods Fifty‐eight endoscopes used at our institution were examined for scratches, discoloration, or deformation in the endoscopic channel using an ultrafine‐diameter scope. Results Damage was observed in seven of the 24 observation endoscopes and 27 of the 34 therapeutic endoscopes, with damage being more common in the therapeutic endoscopes. Scratches were observed in nine of the 25 upper gastrointestinal endoscopes, 23 of the 24 colonoscopes, and one of the two echoendoscopes. Additionally, two colonoscopes, one echoendoscope, and one double‐balloon endoscope showed indentation or narrowing near the curvature. Conclusions The use of an ultrafine‐diameter scope enabled the detection of minute damage and deformations in the channel. Periodic observation with the ultrafine‐diameter scope may promote the long‐term use of the scopes.